Growing Maine’s Foodscape, Growing Maine’s Future - Lindenfeld, Laura; Silka, Linda (Maine Policy Review, 2011)
Maine is experiencing a culinary renaissance. Creativity and entrepreneurship linked with culture and tradition are making Maine a food destination and a unique “foodscape.” Laura Lindenfeld and Linda Silka explore this convergence and its potential to create jobs, protect assets, and support community values.
Keywords: Maine; food culture; foodways; culinary tourism